Basic Income and Labor Supply: Evidence from an RCT in Germany - Sarah Bernhard; Sandra Bohmann; Susann Fiedler; Maximilian Kasy; Jürgen Schupp; Frederik Schwerter (CESifo GmbH, 2025)
How does basic income (a regular, unconditional, guaranteed cash transfer) impact labor supply? We show that in search models of the labor market with income effects, this impact is theoretically ambiguous: Employment and job durations might increase or decrease, match surplus might be shifted to workers or employers, and worker surplus might be reallocated between wages and job amenities. We thus turn to empirical evidence to study this impact. We conducted a pre-registered RCT in Germany, starting 2021, where recipients received 1200 Euro/month for three years. We draw on both administrative and survey data, and find no extensive margin (employment) response, and no impact on on job transitions from either non-employment or employment. We do find a small statistically insignificant intensive margin shift to part-time employment, which implies an excess burden (reduction of government revenues) of ca 7.5% of the transfer. We furthermore observe a small increase of enrollment in training or education.
Keywords: I38; J22; 330; basic income; randomized controlled trial; labor supply